Repertórios musicais em cursos de Pedagogia: narrativas de professoras formadoras - Moreira, Vinicius Ceratti (2020)
The dissertation was developed in the scope of Programa de Pós-Graduação em Educação (PPGE) from the Universidade Federal de Santa Maria (UFSM) and it is linked to the group FAPEM (Formação, Ação e Pesquisa em Educação Musical). The thematic of the research involves the existing relations between Music and Pedagogy, specifically, the musical repertoires that organize training actions in the disciplines of Arts/Music in Pedagogy courses. The general objective of this study is to understand the processes of choices and the implications of the use of musical repertoire of training teachers in Pedagogy courses. As specific objectives, the aim is to get to know the musical trajectories and formations of teachers and how they are articulated with the choices of repertoires for Pedagogy, to investigate which contents - musical and extra-musical - that are developed from the selected musical repertoires, understand how the choices of musical repertoires enhance and move the musical and pedagogical-musical formation of the reference-teacher. The dissertation is organized in a literature review that deals with music in Pedagogy, in the context of Brazilian education. Then, it approaches the studies about musical repertoires for and in teaching, considering data from a mapping in CAPES of academic researches related to the theme. The research for this dissertation had a qualitative approach and the research with narratives was the methodological procedure and the narrative interview with five teacher teachers was used as a data production instrument. Comprehensive-interpretative analysis was used to analyze the findings. The results of this research show that the training teachers choose their musical repertoires based on relationships with life trajectories, activities for the development of musical and extramusical content, the musical tastes of the students and the context of Early Childhood Education. In this way, the choice of repertoires becomes a complex process for the teaching activity and is linked to the ways of thinking and enhancing the musical and pedagogical-musical formation of the reference-teachers.